Integration of Nursing, Physiotherapy, and Health Information Management in Modern Healthcare: A Narrative Review with Implications for the Saudi Healthcare System - Almutairi, Amani Ghunaim; Alharthi, Maryam Abdullah; HALABI, Areej Ahmed Hassan; Alhani, Zainab Abbas Ali; Alhawssawi, Nuha Nouh; Al-Qahtani, Layla Abdullah Saeed; Alsomali, Mona Mohammed; Al-Hadad, Anhar Mohammed; Alfaraj, Zohoor Abdulrahim; Almutairi, Samirah Talaq (Journal of Posthumanism, 2024)
The integration of nursing, physiotherapy, and health information management (HIM) has become increasingly important in modern healthcare systems. Globally, evidence suggests that interdisciplinary collaboration and digital health solutions improve patient outcomes, enhance efficiency, and support system-wide reforms. In Saudi Arabia, Vision 2030 emphasizes healthcare transformation through digital adoption, workforce development, and patient-centered care, making integration across these domains highly relevant.This narrative review aims to synthesize evidence published between 2015 and 2023 regarding the integration of nursing, physiotherapy, and HIM, with a particular focus on implications for the Saudi healthcare system.A narrative review methodology was applied. Literature searches were conducted in PubMed, Scopus, Web of Science, and Google Scholar using terms related to nursing informatics, physiotherapy integration, health information systems, and interprofessional collaboration. Peer-reviewed articles published between 2015 and 2023 were included, with data synthesized thematically to highlight integration benefits, barriers, and policy implications. The review identified significant progress in nursing informatics, particularly with the adoption of electronic health records and decision-support systems. Physiotherapy integration into primary healthcare was shown to improve accessibility and chronic disease management but remains hindered by unclear roles and weak collaboration. HIM demonstrated positive effects on decision-making, patient safety, and data sharing, yet continues to face interoperability and cybersecurity challenges. Saudi Arabia’s Vision 2030 provides an enabling framework for integration, but research gaps persist, especially in physiotherapy and interprofessional education.Integration of nursing, physiotherapy, and HIM offers a pathway to achieving the goals of Saudi Vision 2030 by enhancing care quality, efficiency, and patient outcomes. However, targeted investment in interprofessional education, HIM infrastructure, and physiotherapy workforce development is required. Addressing local research gaps will be critical to developing sustainable, evidence-based models of integrated care in Saudi Arabia.